Right ventricular function in hypertrophic cardiomyopathy: A speckle tracking echocardiography study - (:unkn) unknown (My University, 2015)
0

Objective: The aim of this study was to explore right ventricular (RV) mechanical function in patients with hypertrophic cardiomyopathy (HCM) by 2-D speckle tracking echocardiography (2-D-STE). Methods: Forty-three patients with HCM (mean age 48, 17 females) and 40 healthy subjects were consecutively included in this cross-sectional study. The diagnosis of HCM was based on the presence of typical clinical, electrocardiographic (ECG), and echocardiographic features. Patients with LV systolic impairment, significant valvular disease, history of coronary artery disease, hypertension, malignancy, and chronic obstructive pulmonary disease were excluded. Right and left ventricular (LV) function was assessed by tissue Doppler imaging (TDI) and 2-D-STE. Hypertrophic cardiomyopathy patients were divided into two groups according to ACC/ESC guidelines (LVOT gradient below and above 30 mm Hg). Student t-test was used to compare differences between groups. Non-parametric tests (Mann-Whitney U) were used in cases of abnormal distribution. Results: Hypertrophic cardiomyopathy patients had a significantly larger right atrium and RV diameters compared to controls. Mean pulmonary artery pressures (mPAB) were significantly higher in HCM patients (19.01±13.09 mm Hg vs. 8.40±4.50 mm Hg; p<0.001). Although RV Sm measurements were similar, RV strain measurements (-28.51±5.36% vs. -32.06±7.65%; p=0.016) were significantly lower in HCM patients. Left ventricular global longitudinal, radial, and circumferential strain values were also significantly different between the two groups (-20.50±3.58% vs. -24.12±3.40%; p<0.001, 38.18±12.67% vs. 44.80±10.15%; p=0.012, -21.94±4.28% vs. -23.91±3.95%; p=0.036 consecutively). Rotational movement of LV in each apical, mid-, and basal left ventricular segment was determined, and only mid-ventricular rotation of the HCM patients was more clockwise (-1.71±2.16 ° vs. 0.04±1.72 °; p<0.001). Although mPAP measurements were higher in HCM patients with significant LVOT obstruction (21.52±13.26 mm Hg vs. 12.31±10.53 mm Hg; p=0.049), none of the other TDI or 2-D-STE parameters was significantly different between groups. Conclusion: Speckle tracking echocardiography-derived right ventricular systolic function is impaired in HCM patients when compared with healthy subjects. However, RV systolic function is not affected form LVOT obstruction and left ventricular rotation dynamics in HCM patients.
Keywords: Kalp ve Kalp Damar Sistemi